(untitled) (Innovate Conferences, 2025)
This article presents the results of a study on changes in the particle size distribution of irrigated bog-meadow soils formed in the Umid Nigohi massif in Fergana. It has been demonstrated that, based on the physical clay content (<0.01 mm) in the genetic horizons of these bog-meadow soils, they are classified as heavy loamy and light clays (46.6-62.5%). In terms of mechanical composition, these bog-meadow soils are characterized by a predominance of silt particles.